ENHANCING ONLINE PRIVACY AT THE USER LEVEL: THE ROLE OF INTERNET SKILLS AND POLICY IMPLICATIONS - Büchi, Moritz; Just, Natascha; Latzer, Michael (AoIR Selected Papers of Internet Research, 2016)
Internet users permanently balance the benefits of information disclosure and the risk of privacy incursions. Online privacy has thus become a widely discussed and highly controversial example of rule-making and rule-breaking in the digital age. In market economies, market solutions, self-help, self-organization and self-regulation are in general preferred over state interventions via command and control regulations. In order to understand and govern privacy risks, well-founded knowledge is required on factors that influence the degree of individuals’ self-help. The empirical part of this paper analyzes representative survey data to evaluate what factors explain Internet users’ self-protective privacy behavior online. The results show that general Internet skills best explain the extent to which users actively protect their privacy online while the influence of pro-privacy attitudes and experiences of privacy violations is smaller. Policies aimed at empowering users may therefore promise little success if concerned solely with raising awareness. This directs the attention to governance strategies that foster skill development and ensure that digital skills are developed, maintained and enhanced on a continuous basis.